Broadening the Phenotype Spectrum of MECP2 Variants in Men - Johannes Lötjönen; Venla Kurra; Hannele Laivuori; Nina Bjelogrlić (Molecular Genetics & Genomic Medicine)
ABSTRACT Background MECP2 variants cause X‐chromosome‐linked rare developmental syndromes. Typically, the mutation is sporadic, occurs in females and is fatal in men. Accurate genetic and clinical diagnostics are considered essential for the management of symptoms and the development of new treatments. These aims may be difficult to reach before more is known about factors resulting in highly variable clinical pictures among patients carrying the same MECP2 variant. We describe the clinical picture of two brothers carrying the same MECP2 variant and compare them with cases published in the literature. Methods Most of the MECP2 mutations are known to be de novo mutations, which is why the recurrence of the mutation in the couple's other children is unlikely. Unexpectedly, our routine genetic testing revealed a 23‐year‐old man (P1) and his younger brother (P2) to carry the same hemizygous pathogenic missense variant c.419C>T, p.(Ala140Val) (transcript NM_004992.3) of MECP2, which was found to be inherited from their presumably asymptomatic mother. Thus, further clinical evaluation and comparison with literature cases was considered necessary. Results The P1 has a severe syndromic intellectual disorder (ID), whereas his brother has a substantially milder ID predominantly limited to problems in verbal skills. Neither P1 nor his younger brother has been diagnosed with Rett syndrome. The P1 (unlike his younger brother) has several lingual, social and motor difficulties; disruptive behavior was the most difficult symptom to treat. P1's response to several medical and non‐medical treatment trials has remained inadequate, thus requiring the patient to be hospitalised for a long time. The literature review revealed that apart from our family, there are five other families with more than one male carrying the same MECP2 p.Ala140Val mutation, such as P1 and P2. The phenotypes of all 24 men from us (n = 2) and others (n = 22) carrying the same, presumably non‐lethal mutation show great variability. Conclusions The p.Ala140Val mutation of MECP2 in males is associated with a rare X‐chromosomal developmental disorder with highly variable phenotypes. Further studies are needed to better understand all those influencing factors that can explain phenotypic differences within the same genotype to find optimal medicinal therapies.